Describing the implementation of an innovative intervention and evaluating its effectiveness in increasing research capacity of advanced clinical nurses: using the consolidated framework for implementation research - Gabrielle McKee; Margaret Codd; Orla Dempsey; Paul Gallagher; Catherine Comiskey (BMC, 2017)
Abstract Background Despite advanced nursing roles having a research competency, participation in research is low. There are many barriers to participation in research and few interventions have been developed to address these. This paper aims to describe the implementation of an intervention to increase research participation in advanced clinical nursing roles and evaluate its effectiveness. Methods The implementation of the intervention was carried out within one hospital site. The evaluation utilised a mixed methods design and a implementation science framework. All staff in advanced nursing roles were invited to take part, all those who were interested and had a project in mind could volunteer to participate in the intervention. The intervention consisted of the development of small research groups working on projects developed by the nurse participant/s and supported by an academic and a research fellow. The main evaluation was through focus groups. Output was analysed using thematic analysis. In addition, a survey questionnaire was circulated to all participants to ascertain their self-reported research skills before and after the intervention. The results of the survey were analysed using descriptive statistics. Finally an inventory of research outputs was collated. Results In the first year, twelve new clinical nurse-led research projects were conducted and reported in six peer reviewed papers, two non-peer reviewed papers and 20 conference presentations. The main strengths of the intervention were its promptness to complete research, to publish and to showcase clinical innovations. Main barriers identified were time, appropriate support from academics and from peers. The majority of participants had increased experience at scientific writing and data analysis. Conclusion This study shows that an intervention, with minor financial resources; a top down approach; support of a hands on research fellow; peer collaboration with academics; strong clinical ownership by the clinical nurse researcher; experiential learning opportunities; focused and with needs based educational sessions, is an intervention that can both increase research outputs and capacity of clinically based nurses. Interventions to further enhance nursing research and their evaluation are crucial if we are to address the deficit of nurse-led patient-centred research in the literature.